ENDOTHELIAL PROTECTIVE EFFECTS OF KLYMADINON IN EXPERIMENTAL OVARIECTOMY - A. M. Anishchenko; T. M. Plotnikova (Бюллетень сибирской медицины, 2013)
A Endothelial protective and antithrombogenic effects of Cimicifuga racemosa standardized extract (Klimadynon, Bionorica, Germany) in comparison with ethinylestradiol in experimental ovariectomy were investigated. Extract of Cimicifuga racemosa (klimadynon) contents phytoestrogens, that was the basis for studying of its effects in hypoestrogenic conditions for the purpose of prophylaxis and treatment of cardiovascular complications in climacteric syndrome as an alternatively of hormonal replacement therapy.The course administration of klimadynon (100 mg/kg p.o. daily during 14 days) decelerated the formation of intravascular thrombosis which was initiated by application of 10% FeCb solution on carotid artery. The ethinylestradiol in this conditions intensified prothrombogenic effect of application of 10% FeCh: blood flow in carotid artery stoped to 5 minutes of experiment and mass of the thrombus was on 28% more, than in control rats. For studying of possible mechanisms antithrombogenic action of klimadynon antiplatelet and vasodilator activity of endothelium were studied in rats after bilateral ovariectomy in comparison with effects of ethinylestradiol (25 µg/kg p.o. daily during 14 days). Treatment with klimadynon as well as ethinylestradiol increased the antiplatelet activity of endothelium, restoring its activity to level in sham-operated animals. The endothelium-dependent and endothelium-independence vasodilation by using of acetylcholine (5 µg/kg) and of sodium nitroprusside (30 µg/kg). respectively, were investigated. Coefficient of endothelium dysfunctions (CED) was estimated as ratio: area over curve of arterial pressure after sodium nitroprusside intravenous injection to value of this index after injection of acetylcholine. In rats after bilateral ovariectomy CED was increased by 66% in comparison with CED value in sharm-operated rats. The klimadynon and ethinylestradiol treatment decreased CED on 42% and 28% correspondingly in comparison with values of control group.In summary klimadynon has antytrombogenic and endothelial protective activities in the rats after ovariectomy. The ethinylestradiol decreases endothelial disfunction in ovariectomized rats, but unlike klimadynon demonstrates protrombogenic effect. The present findings suggest that klimadynon could be used as a therapeutic agent for menopausal vascular complication.